Potential Clinical Implications of the Urotensin II Receptor Antagonists - Kane, Emilie; Giaid, Adel (Frontiers in Pharmacology, 2011)
Urotensin-II (UII), which binds to its receptor UT, plays an important role in the heart, kidneys, pancreas, adrenal gland and CNS. In the vasculature, it acts as a potent endothelium-independent vasoconstrictor and endothelium-dependent vasodilator. In disease states, this constriction-dilation equilibrium is disrupted. There is an upregulation of the UII system in heart disease, metabolic syndrome and kidney failure. The increase in UII release and UT expression suggest that UII system may be implicated in the pathology and pathogenesis of these diseases by causing an increase in ACAT-1 activity leading to SMC proliferation and foam cell infiltration, insulin resistance (DMII), as well as inflammation, high blood pressure and plaque formation. Recently, UT antagonists such as SB-611812, palosuran, and most recently a piperazino-isoindolinone based antagonist have been developed in the hope of better understanding the UII system and treating its associated diseases.